Marketing Management - Kumar, Pankaj; Kumar, Pradeep; Yadav, Rahul (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Marketing management is define as it a business discipline which focuses on the practical application of marketing techniques and the management of a firm's marketing resources and activities Globalization has led firms to market beyond the borders of their home countries, making international marketing highly significant and an integral part of a firm's marketing strategy. Marketing managers are often responsible for influencing the level, timing, and composition of customer demand accepted definition of the term. In part, this is because the role of a marketing manager can vary significantly based on a business's size, corporate culture , and industry context. This study wil expand onissues and debates common to many of the approaches and wil conclude with demonstratingthe ability to explain a chosen research approach. This paper has a significant contribution byclarifying how to ensure research quality, which is crucial to pursue auditable data col ectionand analysis and consequently to generate reliable knowledge in particular to case study research.